Parental supervision and discomfort with children walking to school in low-income communities in Cape Town, South Africa. (19th May 2018) - Simons, Abigail; Koekemoer, Karin; Niekerk, Ashley van; Govender, Rajen
ABSTRACT: Objective : The risk of pedestrian injury is compounded for children living in low-income communities due to factors such as poor road and pedestrian infrastructure, reliance on walking as a means of transport, and compromised supervision. Parents play an important role in child pedestrian safety. The primary objective of this study was to examine the effects of child pedestrian variables on parental discomfort with regard to letting their child walk to and from school and on the frequency of adult supervision. Methods : A cross-sectional study was conducted using a convenience sample from 3 schools participating in a pedestrian safety school initiative. The schools are situated in low-income, high-risk communities in the City of Cape Town. A parent survey form was translated into isiXhosa and sent home with learners to those parents who had consented to participate. The response rate was 70.4%, and only parents of children who walk to and from school were included in the final sample ( n = 359). Child pedestrian variables include the time taken to walk to school, parental rating of the child's ability to safely cross the road, and the frequency of adult supervision. Results : More than half of parents reported that their child walked to and from school without adult supervision. About 56% of children took less than 20 min to walk to school. Most parents (61%) were uncomfortable with their child walking to school, although the majority of parents (55.7%) rated their child's ability to cross the road safely as better or significantly better than average (compared to peers). The parents did not perceive any differences in pedestrian risk factors between boys and girls or between younger (6–9 years) and older (10–15 years) children. The time spent by a child walking to school and parents' perceptions of their child's road-crossing ability were found to be significant predictors of parental discomfort (in letting their child walk). Younger children and children who spent less time walking were more likely to be supervised by an adult. Conclusions : Many South African schoolchildren have to navigate the roads without adult supervision from a young age. Caregivers, especially in low-income settings, often have limited options with regard to getting their child to school safely. Regardless of the child's age and gender, the time that they spend on the roads is an important factor for parents in terms of pedestrian safety.